Aqaba Quraysh in the poetry of Ubaid Allah bin Qais Al-Ruqayyat (Journal of the College of Basic Education, 2022)
The Umayyad era witnessed 132-41 (AH) rule, inheritance, and a new social and cultural construction, the birthplace of thatWith the development of other fields of science, including (intellectual, scientific, economic and literary) on a large scale Especially in the environment of the Hijaz, in addition to that, the era witnessed the expansion of the conquest movement in it, despite theThe presence of a party, unrest, civil strife, internal revolts, and violent political struggles over the succession are all This led to the revival of the literary movement, especially political poetry and the poetry of Islamic schools of thought.